2021
DOI: 10.1080/01612840.2020.1867675
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic-Specific Factors Related to Generalized Anxiety Disorder during the Initial COVID-19 Protocols in the United States

Abstract: Little is known about the psychological stress and secondary impacts emerging among the general U.S. population as a result of the ongoing COVID-19 pandemic. The purpose for the current study is to assess the prevalence rates of Generalized Anxiety Disorder (GAD) and to establish psychosocial correlates, pandemic-themed concerns, and other comorbidities for those with GAD at the initial onset of the COVID-19 pandemic. This online study included 2,101 U.S. adults between April 14-22, 2020, during the initial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
0
20
1
Order By: Relevance
“…Previous studies showed that symptoms of anxiety and depression were reported in 25.5–44.6% and 12.1–50.4% of HCWs treating patients with COVID-19 4 16 43 and in 46.5–77.4% and 22.8–74.2% of HCWs treating patients with SARS, 33 44 45 46 respectively. The relatively lower rate of psychological distress compared to that in other countries, especially generalized anxiety of the HCWs in the present study, may be due to the differences in the number of confirmed cases, differences in working environment, using different measures, and varying organizational communication and support, 47 48 etc.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies showed that symptoms of anxiety and depression were reported in 25.5–44.6% and 12.1–50.4% of HCWs treating patients with COVID-19 4 16 43 and in 46.5–77.4% and 22.8–74.2% of HCWs treating patients with SARS, 33 44 45 46 respectively. The relatively lower rate of psychological distress compared to that in other countries, especially generalized anxiety of the HCWs in the present study, may be due to the differences in the number of confirmed cases, differences in working environment, using different measures, and varying organizational communication and support, 47 48 etc.…”
Section: Discussioncontrasting
confidence: 60%
“…The percentages of moderate-to-severe anxiety in China and the UK were lower before the COVID-19 pandemic [18,19]. A substantially lower prevalence of anxiety symptoms before the pandemic as compared to the pandemic has also been reported for the United States of America (17.9%) [20] and the German adult population (44.9%) [21]. Hetkamp and colleagues found that six weeks after the lockdown, anxiety levels in the general population of Germany remained elevated [22].…”
Section: Introductionmentioning
confidence: 84%
“…GAD is a prevalent type of anxiety; the lifetime prevalence of GAD is 6.2% for patients between the ages of 18 and 64 years old [ 8 ]. The prevalence of GAD has been rising since the start of the SARS-CoV-2 pandemic [ 10 ]. While the underlying pathophysiology of GAD is still an area of investigation, it is currently believed to result from abnormalities within the serotonergic and noradrenergic systems [ 11 ].…”
Section: Introductionmentioning
confidence: 99%